Creative self-realization as condition social-psychological adaptation to personality - I V Кulagina (Peoples' Friendship University of Russia (RUDN University), 2010)
The Article is dedicated to analysis result, got in the course of experimental study of the particularities self-realization of students with different level social-psychological adaptation.